INNOVATIVE METHODS OF CHILDREN PREPARATION TO SCHOOL (Scientific journal of the Fergana State University, 2023)
In the article, the innovative approaches of the preschool education organization and cooperation with the family in preparing children for school are widely covered. Aspects and peculiarities of mandatory one-year preparation of children for primary education in the organization of preschool education are widely analyzed.